Simulating the process of hydrodesulphfurisation (HDS) of light cycle oil (LCO) in Dung Quat refinery - Ninh, Le Huu; Hien, Nguyen Thi Minh; Quang, Nguyen Danh; Thanh, Diep Ngoc; Thai, Nguyen Trong (Petrovietnam Journal, 2015)
This research was conducted to simulate the process of LCO hydrodesulphurisation in Dung Quat refinery using UniSim Design. The simulation is based on the kinetics of 44 sulfur compounds and on conditions and parameters (mass flow rates, temperature and pressure readings) obtained from LCO Hydrotreater 024 of Dung Quat refinery. The HDS was carried out in the Plug Flow Reactor (PFR). The results obtained from the HDS-PFR model were compared with the operating results of LCO Hydrotreater 024 in Dung Quat refinery and the results obtained from the HDS-ASPEN model.